EFFECT OF DIFFERENT LEVEL OF CONCENTRATE FEEDING ON HEMATOBIOCHEMICAL PARAMETERS IN AN EXPERIMENTALLY INDUCED SUB ACUTE RUMINAL ACIDOSIS (SARA) IN SHEEP AND ITS MANAGEMENT WITH DIFFERENT CONCENTRATION OF ANTACIDS - A. S. Chaudhry; M. A. Khan; M. S. Khan; K. Ashraf; M. H. Saleem; N. U. Khan; T. Usman; I. Ahmad (Journal of Animal and Plant Sciences, 2018)
The study was designed to detect the effect of SARA on hematobiochemical parameters and efficacy of some allopathic and herbal antacid drugs against SARA. A total of 16 sheep of the same age and weight were divided randomly into four groups.  Group A was placed as a control group and fed on routine diet while Group B, C and D were fed on Barseem with 250 gm, 500 gm and 750 gm ground wheat flour, respectively to induce SARA. Blood samples were collected three times per day for five consecutive days and analyzed for blood parameters using calibrated blood gas analyzer. A significant increase was recorded in WBC count, whereas, non significant differences were observed in all other blood parameters. During therapeutic trials different concentration of antacids were used and their efficacy was analyzed.  The 12 animals in which SARA were induced were selected and divided into 3 groups. The Group 1 and Group 2 were treated with different concentration of sodium bicarbonate, whereas, Group 3 was fed with monensin and SAFI. The ruminal fluid showed marked decrease in pH and increase in serum haptoglobin and WBC counts, but no change in other blood parameters was observed in any of the three groups.
Keywords: SARA; prevalence; herbal buffer SAFI; ruminal fluid pH